Data Sovereignty on the Brink: A Review of the Causes of Public Sector Data Leaks and Their Impact on Intelligence Stability - Sigit Setiono (Security Intelligence Terrorism Journal (SITJ), 2026)
Data leaks in the public sector have become an existential threat to Indonesia's digital sovereignty and national information amidst the massive digitization of bureaucracy through the Electronic-Based Government System (SPBE). While SPBE improves service efficiency, this integration simultaneously expands the attack surface for various threat actors. This research aims to analyze the systemic causes of data leaks in government agencies and their profound implications for the stability of the country's intelligence services. Using descriptive qualitative methods through a case study approach and a review of recent cyber incidents, this research identifies that the primary vulnerabilities stem from the human factor as the weakest link—reflected in low security literacy among state officials—and weak information security governance resulting from fragmented cyber infrastructure and inter-agency sectoral egos. Furthermore, the aggressiveness of Advanced Persistent Threat (APT) actors serves as an external catalyst that exacerbates this situation. The research findings indicate that the impact of data leaks goes beyond technical losses and individual privacy; they create systemic intelligence risks that undermine the country's counterintelligence and early detection functions. This phenomenon exposes strategic data to state-sponsored actors, facilitates cyber espionage, and delegitimizes public trust in the government. As a strategic solution, the author recommends strengthening national cyber resilience through the integration of a centralized security architecture integrated with intelligence functions, as well as regulatory reforms that are more responsive to the dynamics of hybrid threats to protect national digital sovereignty.